(untitled) (Proceedings of the International Conference of Geological Engineering Faculty, 2021)
Walini, Cikalongwetan District, West Bandung Regency is one of the 3 plans for the relocation of the capital city of West Java. This area is also projected to become a high-speed train station from Bandung City to Jakarta. This paper is aimed to reveal the feasibility of the Walini area based on landslide potentials. The methodology of this research is the Weighted Linear Combination (WLC) method using the parameters of Landslide Hazard Assessment parameters (rainfall, geology, slope, elevation, vegetation) and Landslide Vulnerability Assessment parameters (population, LULC, proximity to the road, proximity to stream). The results show that this area has 5 classes of risk, from Very Low to Very High. Kanangasari Village is filled by Moderate to Very High Class but the dominant class is High with an area 8,179 km2 (68,01% of the area). Mandalasari and Mandalamukti are in High to Very High Class. Very High Class in Mandalamukti is 4,959 km2 (86,5% of the area). Meanwhile, Mandalasari has 7,906 km2 (62,7% of the area) of Very High Class. It can be concluded that the Walini area is less suitable as a candidate for the capital city of West Java and the High-Speed train station based on landslide disaster because the potential risk of Very High class is up to 50 % and High class is 40% of the total are